Respiratory symptoms as initial manifestations of interstitial lung disease in clinically amyopathic juvenile dermatomyositis: a case report with literature review - Jingyi Xia; Gaoli Jiang; Tingting Jin; Quanli Shen; Yangyang Ma; Libo Wang; Liling Qian (BMC, 2021)
Abstract Background Clinically amyopathic juvenile dermatomyositis (CAJDM) is a clinical subgroup of juvenile dermatomyositis (JDM), characterized by JDM rashes with little or no clinically evident muscle weakness. Interstitial lung disease (ILD) is an uncommon but potentially fatal complication of juvenile dermatomyositis (JDM). While adults with dermatomyositis-associated ILD usually present respiratory symptoms before or at the same time as skin muscle manifestations, only a few studies have covered the onset of respiratory symptoms of ILD in JDM patients, especially CAJDM. There is currently no clear effective treatment regime or any prognostic factors for CAJDM-associated ILD. Case presentation Here, we report the first case of a CAJDM patient who presented with respiratory symptoms as the initial manifestation. A 10-year-old male patient presented to the hospital with a complaint of progressive cough and chest pain. Violaceous macule and papules appeared a few days later and he was positive for anti-Ro-52 antibodies. Imaging showed diffuse interstitial infiltration in both lungs and lung function tests showed restrictive and obstructive ventilatory dysfunction. Muscular abnormalities were excluded by thigh magnetic resonance imaging (MRI) and electromyography. Skin biopsy showed pathognomonic findings consistent with DM. Lung biopsy indicated chronic inflammation of the mucosa. This patient was finally diagnosed with CAJDM complicated by ILD and prescribed methylprednisolone, immunoglobulin, prednisolone and mycophenolate mofetil (MMF) for treatment. The patient's cutaneous and respiratory manifestations were largely improved. We retrospectively reviewed this and another six cases with CAJDM-associated ILD reported previously to better understand its clinical characteristics and effective management. Conclusions Initial respiratory symptoms with rapid progression in patients presenting Gottron papules should be considered manifestations of CAJDM-associated ILD. We also found a combination of corticosteroids, IVIG and MMF to be an effective method of arresting the progress of CAJDM-associated ILD and improving the prognosis of the patients.